2017
DOI: 10.1111/1754-9485.12682
|View full text |Cite
|
Sign up to set email alerts
|

National survey on image‐guided radiotherapy practice in New Zealand

Abstract: Image-guided radiotherapy is widely used in NZ; however, there is a wide variation in its application between centres. Detailed tumour site-specific, imaging modality-specific national guidelines will allow standardization of IGRT practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 19 publications
(52 reference statements)
3
19
0
Order By: Relevance
“…Modern EBRT techniques and IGRT modalities were widely available and accepted, marking a trend that has been described in previous surveys (2007-2017; Table 3) (9-14). Sophisticated high-precision techniques using smaller margins require high-standard (daily online) image guidance (13,24). For example, IMRT/VMAT techniques lead to a steep dose gradient, where IGRT becomes extremely important to prevent the risk of partially missing the target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern EBRT techniques and IGRT modalities were widely available and accepted, marking a trend that has been described in previous surveys (2007-2017; Table 3) (9-14). Sophisticated high-precision techniques using smaller margins require high-standard (daily online) image guidance (13,24). For example, IMRT/VMAT techniques lead to a steep dose gradient, where IGRT becomes extremely important to prevent the risk of partially missing the target.…”
Section: Discussionmentioning
confidence: 99%
“…IGRT practices among adult cancer patients have been reported in multiple studies (9)(10)(11)(12)(13), showing a tendency towards an increased IGRT use over time. A British survey in 2008 showed that routine IGRT use was low (8%), and that 25% of surveyed institutes intended to implement IGRT within a year (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrument validity was measured by first acquiring a CT of the phantom–bolus assembly (Philips Brilliance Big Bore CT, Philips Healthcare, Amsterdam, Netherlands), importing the dataset to Pinnacle treatment planning system (version 9.10, Philips Medical Systems, Amsterdam, Netherlands), profiling the electron densities of the phantom, wax and bolus sheets and comparing these to established values . Soft tissue densities were 1.1 g/cm 3 , bone was 1.7 g/cm 3 and adipose tissue was 0.9 g/cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Cone‐beam computed tomography (CBCT) is one option for image verification, with implementation undergoing a surge in Australia and New Zealand. Recent 2015–2016 surveys show that CBCT was available in 97% of Australian departments and in 86% of New Zealand departments compared with 8% of departments in this region having CBCT just a decade ago . Despite being available in almost all departments, CBCT has not replaced other image verification modalities, with kilovoltage (kV) planar imaging being the second most common imaging tool used in IGRT …”
Section: Introductionmentioning
confidence: 99%